1990
DOI: 10.2134/agronj1990.00021962008200060011x
|View full text |Cite
|
Sign up to set email alerts
|

Planting Date and Nitrogen Rate Effects on Spring Malting Barley

Abstract: Planting date (D) and N fertilizer have been shown to significantly increase spring malting barley (Hordeum vulgare L.) grain yield and protein when grown under dryland production systems where water is limiting. This study was conducted to determine D and N rate effects on grain yield, grain protein, kernel plumpness and yield components of spring malting barley grown under a production system that minimized crop water stress. Between 1984 and 1988, 'Klages' barley was planted at 2-wk intervals between 15 Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
35
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 12 publications
8
35
0
Order By: Relevance
“…1D) indicating a direct impact of N rate on malting barley quality. Previous studies have also shown that N fertilizer rate was a major factor aff ecting malting barley yield and quality and could result in decreased kernel plumpness and increased protein concentration (Lauer and Partridge, 1990;McKenzie et al, 2005;Th errien et al, 1994).…”
Section: Effect Of Nitrogen Ratementioning
confidence: 99%
“…1D) indicating a direct impact of N rate on malting barley quality. Previous studies have also shown that N fertilizer rate was a major factor aff ecting malting barley yield and quality and could result in decreased kernel plumpness and increased protein concentration (Lauer and Partridge, 1990;McKenzie et al, 2005;Th errien et al, 1994).…”
Section: Effect Of Nitrogen Ratementioning
confidence: 99%
“…Typically, the highest grain yields are achieved with the earliest feasible seeding date, with initially a gradual decline, then a much more rapid decline when seeding is delayed (Beard 1961;McFadden 1970;Ciha 1983;Lauer and Partridge 1990;Juskiw and Helm 2003). The impact of delayed seeding on grain yield varies among years and cultivars (Ciha 1983;Juskiw and Helm 2003).…”
mentioning
confidence: 99%
“…Yield losses may be as high as 50% when seeding is appreciably delayed due to increased disease (Nass et al 1975), shorter vegetative and grain-filling periods (Juskiw and Helm 2003), and higher vapour pressure deficits/lower water use efficiency (Tanner and Sinclair 1983). In addition to yield loss, malting quality is often lower in late-seeded crops due to a reduction in the proportion of kernels that are plump and, in many cases, increased grain protein (Beard 1961;Lauer and Partridge 1990;Weston et al 1993;Juskiw and Helm 2003).…”
mentioning
confidence: 99%
“…1B). Previous studies have shown barley kernel plumpness usually decreased with increasing N rate but the results were sometimes inconsistent among locations and years (Zubriski et al 1970;Lauer and Partridge 1990;McKenzie et al 2005;O'Donovan et al 2011). Preceding crop had no effect on either germination energy or germination index while N rate had no effect on germination energy (Tables 1 and 2).…”
Section: Grain Quality Parametersmentioning
confidence: 95%